Significance of the drug-induced lymphocyte stimulation test for various oral mesalamines in ulcerative colitis with mesalamine intolerance - Akira Madarame; Masakatsu Fukuzawa; Kumiko Uchida; Tadashi Ichimiya; Sakiko Naito; Yoshiya Yamauchi; Takashi Morise; Yasuyuki Kagawa; Takahiro Muramatsu; Takao Itoi (PLoS ONE, 2025)
This study aimed to determine if the drug-induced lymphocyte stimulation test (DLST) for various oral mesalamines can diagnose mesalamine intolerance and predict the success of retreatment in patients with adverse events (AEs) due to the first oral 5-aminosalicylate (5-ASA) formulations administered. Data from patients with ulcerative colitis who experienced AEs after administration of the first oral 5-ASA and underwent DLSTs for two or more types of mesalamine, including the first oral 5-ASA were retrospectively analyzed. Mesalamine intolerance was defined as AEs within 6 months of starting the first oral 5-ASA and the inability to take oral mesalamine. Clinical characteristics, symptoms, type of first oral 5-ASA, DLST results, and the efficacy of retreatment with oral mesalamine were compared. The DLST for the first oral 5-ASA (F-DLST), highest DLST among the different oral mesalamine types (H-DLST), and mean DLST (M-DLST) were analyzed. Twenty-eight patients (median age 39 years, 57.1% male) were eligible; six patients were tolerant to oral mesalamine and22 were intolerant. Positive F-DLST (odds ratio [OR], 2.300; p = 0.002), positive M-DLST (OR, 2.667; p = 0.007), and older age at diagnosis (median 24.5 vs. 41.5; p = 0.006) were associated with mesalamine intolerance. Fourteen of the 28 patients underwent mesalamine retreatment. Higher F-DLST (median 88.0 vs. 174.0; p = 0.026), M-DLST (median 118.5 vs. 170.3; p = 0.040), and older age at diagnosis (median 24.5 vs. 39.0; p = 0.033) were associated with retreatment failure for oral mesalamine. DLSTs for various oral mesalamine formulations may be useful in predicting mesalamine intolerance and retreatment outcomes. However, their clinical utility should be interpreted with caution due to the risk of false-positive and false-negative results.